Quality Imports and Quality Exports: Micro Evidence from China. Issue 1 (2nd January 2020) - Li, Hongbing; Cai, Hongbo; Lin, Xuedong; Gu, Junyi
ABSTRACT: Detailed micro-level data of enterprises between 2000 and 2007 are adopted to study the influence of quality of imports on quality of similar exports in general trade and processing trade. Results indicate that quality of competitive imports in general trade exerts a significant and stable promoting effect on quality of similar exports, but in processing trade bears an inverted U-shaped relationship. The competitive imports with higher quality gradient exert a more promoting effect on quality of similar exports. The competitive imports with higher quality from a certain exporter exert a higher promoting effect on similar exports of Chinese enterprises to the country. The innovation-driven quality improvement of competitive imports in general trade significantly improves quality of similar exports. Furthermore, the quality of competitive imports exerts the highest promoting impact on quality of exports in the monopoly and labor-intensive industries, while it exerts a small effect on those in the capital-intensive industries.